Ultrasound Measurement of Fetal Kidney Length in Normal Pregnancy and its Correlation with Gestational Age - Koirala, Sapana; Adhikari, Kapil; Devkota, Karun (Journal of Nepal Health Research Council, 2023)
Background: To establish a nomogram of fetal kidney length for a normal pregnancy from 20 to 41 weeks of gestational age. Methods: A prospective cross-sectional study was carried out in the Department of radio-diagnosis and imaging BPKIHS, Dharan. 400 kidneys of 200 fetuses between the gestational age 20 to 41 weeks were scanned. Renal measurement was performed by ultrasonography. Results: Analysis was performed on data obtained from 200 normal fetuses. Size charts for right, left and mean fetal kidney length with standard deviation were presented for each weeks of gestation from 20 weeks to 41 weeks. The difference in renal length between right and left side was statistically not significant.There was significant correlation between gestational age and fetal kidney length (r=0.947, p=0.001).Conclusions: Fetal kidney length can be used as an adjunct parameter for estimation of gestation age.Keywords: Fetal kidney; gestational age; ultrasound